Advanced Endoscopic Endonasal Approach to the Pterygopalatine Fossa and Orbit: The Endoscopic Tri-port Approach - Omura, Kazuhiro; Nomura, Kazuhiro; Mori, Ryosuke; Ishii, Yudo; Tanaka, Yasuhiro; Otori, Nobuyoshi; Kojima, Hiromi (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective The pterygopalatine fossa (PPF) is a narrow space situated posterior to the maxillary sinus. While external approaches have been used to treat tumors of the PPF, recent endoscopic approaches have become favored as an alternative; we developed an endoscopic tri-port approach, which provides wide surgical corridor with minimal invasion, for PPF. This report aims to introduce and verify the new approach.Design Case series.Setting A tertiary referral hospital.Participants We reviewed 11 patients with PPF or orbital tumors who were treated with the endoscopic tri-port approach.Main Outcome Measures Accessing tri-port approach's effects and limitations.Results When the tumor was located in the PPF or orbit without intracranial invasion, en bloc resection was achieved in six patients. With the exception of one patient, the nasal septum was preserved if not used for skull base reconstruction. If not invaded by a tumor or necessary for reconstruction, the inferior and middle turbinates were preserved.Conclusion The endoscopic tri-port approach provides an excellent surgical view and wide corridor and not requires an external approach, including a gingival incision.
Keywords: endoscopic sinus surgery; endoscopic skull base surgery; minimally invasive surgery; pterygopalatine fossa; tissue preservation